2013
DOI: 10.1111/tmi.12072
|View full text |Cite
|
Sign up to set email alerts
|

Loss to follow‐up before and after delivery among women testing HIV positive during pregnancy in Johannesburg, South Africa

Abstract: Objective HIV-positive pregnant women are at heightened risk of becoming lost to follow-up (LTFU) from HIV care. We examined LTFU before and after delivery among pregnant women newly-diagnosed with HIV. Methods Observational cohort study of all pregnant women ≥18 years (N=300) testing HIV-positive for the first time at their first ANC visit between January–June 2010, at a primary healthcare clinic in Johannesburg, South Africa. Women (n=27) whose delivery date could not be determined were excluded. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 27 publications
7
115
1
Order By: Relevance
“…In an analysis from South Africa 9.9% of the patients who achieved virologic suppression on first-line ART during pregnancy developed virologic failure a median of 16 months from ART initiation [27]. This finding from a single site non-governmental organization managed adult ART and PMTCT clinic is lower than our finding of 16% failure among those with pre-partum virologic suppression.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In an analysis from South Africa 9.9% of the patients who achieved virologic suppression on first-line ART during pregnancy developed virologic failure a median of 16 months from ART initiation [27]. This finding from a single site non-governmental organization managed adult ART and PMTCT clinic is lower than our finding of 16% failure among those with pre-partum virologic suppression.…”
Section: Discussioncontrasting
confidence: 66%
“…Depression may have contributed to poor adherence, as has been previously reported [11, 25, 26]. Financial constraints, employment, stigma, and disclosure may also have reduced adherence but were not evaluated [10, 27]. Notably, we did not observe an association with either TB treatment or having initiated ART prior to pregnancy and treatment failure.…”
Section: Discussionmentioning
confidence: 58%
“…Their inclusion in the study cohort might have increased overall short-term losses to care as reported elsewhere. 30,31 Lastly, despite basic interventions to ensure fidelity, no specific data were collected to report on fidelity to the piloted model. The present study highlights useful directions for future research.…”
Section: Discussionmentioning
confidence: 99%
“…A recent South African study found that 58% of HIV-infected pregnant women testing positive for HIV during pregnancy were lost-to-care by six months postpartum (7). Although early reports from Malawi suggested that Option B+ programs can retain patients at levels comparable to retention of non-PMTCT patients (8), more recent data from across 540 Malawian health centers indicate that women who start HAART as part of the Option B+ program were five times more likely not return to the clinic after HAART initiation as compared to women who were started on treatment due to low CD4 cell counts (9).…”
Section: Introductionmentioning
confidence: 99%